Type II Colonic Atresia and High Anorectal Malformation: A Rare Coexistence and Literature Review - Prasanta Kumar Tripathy; Pradeep Kumar Jena (JCDR Research and Publications Pvt. Ltd., 2017)
Colonic atresia and anorectal malformation are congenital anomalies affecting distal gastrointestinal tract. Individually, both the anomalies need urgent surgical and medical care for survival of the newborn. However, the association between them is reported only in a handful of cases and very little information is available regarding the management of the combined anomaly. We came across a three-day-old male neonate having Type II colonic atresia along with high anorectal malformation. Because of the rarity and unique challenges needed for management of both the anomalies, this case is being reported with review of relevant literature.